Development and performance of particleboard from various types of organic waste and adhesives : A review - Mohd Nazif, Baharuddin; Norazwani, Muhammad Zain; Wan Sharuzi, Wan Harun; Eida Nadirah, Roslin; Farizah Adliza, Ghazali; Siti Norzailina, Md Som (Elsevier Ltd, 2023)
Environmentally friendly or green building materials are more commonly used in the construction industry and furniture making industry. The knowledge of the environmental risks including the depletion of natural resources, the impact of pesticides, as well as the amplifier and enforcement criteria of good practice have led to an increase in the practice of recycling waste materials, and in particular, the recycling of abandoned trees in particleboard production. From the adhesive aspect, in view of future constraints of formaldehyde use, suitable alternatives to formaldehyde-based adhesive systems would have to be developed and implemented in the wood processing industry. The present review represents a critical appraisal of various organic wastes and adhesives used as raw materials in particleboard development. The core of this review is an assessment of physical and mechanical properties of particleboards based on various types of organic waste and adhesive. Based on these data, we evaluated their potential to identify suitable alternative raw materials having a certain probability to meet the requirements of a large-scale industry sector. Characteristics such as density, thickness swelling, modulus of rupture (MOR) and modulus of elasticity (MOE) are significant in the studies carried out by researchers worldwide. However, they also depend on the types of raw materials, adhesives, parameters and indicators used throughout particleboard production. As an overall conclusion, some organic wastes have the potential to replace wood fibers as raw materials in particleboard production with similar performances. Natural-based adhesives have also shown the potential to substitute formaldehyde-based adhesives in terms of performance. However, toxicological investigations should be performed before a decision can been made to ensure they are safe and add value as replacements for formaldehyde-based adhesives.